Desenvolvimento e caracterização de microssatélites, mapeamento genético e identificação de QTL para tempo de cocção em Phaseolus vulgaris - Garcia , Robertha Augusta Vasconcelos (2009)
From the 50 described species of the Phaseolus genera, Phaseolus vulgaris (common bean) is the most cultivated in the world and occupies 85% of the total production area. Brazil has an outstanding position in the world scenario and is considered the main grower, contributing with 17.58% of total production in an area estimated in 4.01 million hectares. Among grain legumes, common bean is the most important for direct human consumption, representing an important source of protein, amino-acids and minerals in the diet of Brazilian population. Breeding programs have searched for ways to increase productivity and simultaneously enhance its nutritional value and decrease the cooking time. The demand on the use of molecular tools has increased in the past few years, aiming to generate information that can be used in genetic breeding programs. This work presents two studies that were conducted from the development of a set of microsatellite markers derived from expressed sequences and genomic libraries. In the first study EST-SSR markers developed with a set of genomic SSR were evaluated for their amplification quality, transferability, genic information content and polymorphism in the Bat 93 x Jalo EEP558 population study. A total of markers 377 EST-SRR were developed, from which 80% showed PCR amplification products. For the transferability analysis 65 EST-SSR and an additional set of 102 genomic SSR were selected, from which 82% were transferred to, at least, one of the 10 legume species evaluated, where the higher amplification rate was observed between species from the Phaseolus genera (63.67%) and the lower was observed for the Arachis (1.8%). In the characterization of 167 SSR, 72% were polymorphic and the mean estimated PIC varied from 0.53 for genomic SSR to 0.47 to EST-SSR. The analysis of polymorphism in the BJ population revealed that from the 315 markers (302 EST - SSR and 13 genomic), 24% were polymorphic and incorporated to the common bean reference map, totalizing 180 mapped loci with a total map distance of 1154.63cM. The second study presents the construction of a genetic map using a population derived from the cross CNFM 7875 x Laranja, where 132 families were obtained and evaluated in three generations, three locations and four experiments where the genotypic data were obtained. A set of 1,034 SSR loci were tested for polymorphism and 105 (10%) were polymorphic and 93 were mapped on 12 linkage groups with a total map length of 1,369.9cM. The analysis of the phenotypic data indicated that the families show great variability for cooking time. The coefficients of heritability between the means varied between 42.89% and 62.85%. QTL mapping was performed using composite interval mapping and eight regions were associated to the control of this trait, varying from 2 to 4 QTL in generations F2:3 e F2:5, respectively. Significant interactions were observed between QTL and locations, but one QTL was stable between generations conducted in the same environment. The proportion of the phenotypic variation explained by the QTL varied from 3.35% to 21.77%.